Liquid-Embolic Assisted Retrograde Transvenous Obliteration of Bleeding Gastric Varices: The LARTO Technique - Bajaj, Suryansh; Rohilla, Mili; Ramjit, Amit; Wadhwa, Vibhor (Journal of Clinical Interventional Radiology ISVIR, 2025)
Balloon-occluded retrograde transvenous obliteration (BRTO) has been an established technique for treating bleeding gastric varices. However, the traditional BRTO technique requires prolonged balloon inflation and can be resource-intensive. Advanced variations of classic BRTO technique using coils (CARTO) or plugs (PARTO) have been described, but can be cost prohibitive. The authors report a novel variation – liquid-embolic assisted retrograde transvenous obliteration (LARTO) – utilizing the LAVA liquid embolic system to occlude the outflow vein during variceal obliteration, instead of coils or plugs.
Keywords: BRTO; LARTO; liquid-embolic assisted retrograde transvenous obliteration; LAVA; liquid embolic